2010
DOI: 10.1111/j.1365-2966.2010.17549.x
|View full text |Cite
|
Sign up to set email alerts
|

The properties of the interstellar medium within a star-forming galaxy at z= 2.3

Abstract: We present an analysis of the molecular and atomic gas emission in the rest-frame far-infrared and submillimetre from the lensed z = 2.3 submillimetre galaxy SMM J2135−0102. We obtain very high signal-to-noise ratio detections of 11 transitions from three species and limits on a further 20 transitions from nine species. We use the 12 CO, [C I] and HCN line strengths to investigate the gas mass, kinematic structure and interstellar medium (ISM) chemistry and find strong evidence for a two-phase medium within th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
146
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(164 citation statements)
references
References 90 publications
16
146
2
Order By: Relevance
“…No emission is detected in this stack with a 1σ flux limit of 0.06 Jy km s -1 (assuming a linewidth of 400 km s -1 ). This non-detection is consistent with the few detections of dense molecular gas tracers in high-redshift objects that are significantly fainter than the CO emission [45][46][47][48][49][50][51][52][53][54] . Also, no stacked detection was achieved using different combinations of high density tracers (e.g.…”
Section: Stacking Of Fainter Lines In the Frequency Scansupporting
confidence: 86%
“…No emission is detected in this stack with a 1σ flux limit of 0.06 Jy km s -1 (assuming a linewidth of 400 km s -1 ). This non-detection is consistent with the few detections of dense molecular gas tracers in high-redshift objects that are significantly fainter than the CO emission [45][46][47][48][49][50][51][52][53][54] . Also, no stacked detection was achieved using different combinations of high density tracers (e.g.…”
Section: Stacking Of Fainter Lines In the Frequency Scansupporting
confidence: 86%
“…The lensing flux density enhancement has also allowed studies, for the first time at high redshifts, of the spectral line energy distributions (SLEDs) of 13 CO and C 18 O from J = 1 − 0 to J = 7 − 6 transitions of this galaxy Danielson et al (2013). The 13 CO emission from optically thin regions imply a total gas mass for the galaxy of ∼ 1.5 × 10 10 M and a conversion of CO to H 2 mass α CO ∼ 0.9, consistent with bright SMG-like DSFGs for a ULIRG system at z ∼ 2.…”
Section: Smm J2135-0102: the Cosmic Eyelashmentioning
confidence: 99%
“…In combination, Ivison et al (2010d) has suggested that the galaxy contains kpc-scale starburst clumps distributed over a large disk, different from nuclear starbursting local ULIRGS. Further PDR modeling using a combination of 12 CO, [CI], and HCN line intensities are presented in Danielson et al (2011).…”
Section: Smm J2135-0102: the Cosmic Eyelashmentioning
confidence: 99%
“…As the J transition increases, the peak of local emissivity occurs at lower and lower AV, which can then provide information about the state of PDRs in these conditions. Previous work presenting PDR analyses of molecular and atomic emission lines in DSFGs (e.g., Danielson et al 2011;Alaghband-Zadeh et al 2013) have generally used the well-known Kaufman et al (1999) PDR models. There are, however, a number of critical parameters that affect the PDR modelling results, which the Kaufman et al (1999) models do not account for.…”
Section: Pdr Modellingmentioning
confidence: 99%